Penerapan slow deep breathing terhadap fatigue pada pasien gagal ginjal yang menjalankan hemodialisa: sebuah tinjauan sistematis - Anggriani Utama, Yofa (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Chroniic kiidneiy diiseiasei or chroniic reinal faiilurei ranks as thei 20 th leiadiing causeiof deiath worldwiidei iin Iindoneisiia, chroniic kiidneiy faiilurei ranks 10 th among causeis of deiath. Chroniic kiidneiy faiilurei iis a condiitiion iin whiich thei kiidneiys do not functiion propeirly duei to kiidneiy damagei, whiich can bei treiateid wiith heimodiialysiis, causiing physiical weiakneiss, deicreiaseid eineirgy, and fatiiquei duei to compliicatiions from heimodiialysiis. Thei purposei of thiis study was to deiteirmiinei thei eiffeict of slow deieip breiathiing on fatiiquei iin kiidneiy faiilurei patiieints undeirgoiing heimodiialysiis. Baseid on thei reisult of systeimatiic reiviieiw, iit was found that slow deieip breiathiing theirapy has an affeict on fatiiquei iin kiidneiy faiilurei patiieints undeirgoiing heimodiialysiis.